Ponte de ligação entre redes automotivas veiculares - Conrado, Cezar Henrique (2024)
The purpose of this thesis is to design and build a prototype that establishes a connecting bridge between two heavy vehicle communication networks. The standard J1939/CAN was established in 2000 by the Society of Automotive Engineers (SAE) as automotive protocol to replace the J1708/J1587 network. However, it is a common practice in automotive industry that obsolete systems coexist with updated systems. Therefore, the prototype will be presented with the ability to request information from the J1587 network through the J1939 network in an adaptive way, where the operator can choose via CAN message which data you want to retrieve from the other network. In this way, the aim is to overcome alternatives already present on the market, where the operator is restricted to a pre-established list of messages.